(untitled) (caleidoscópio: literatura e tradução, 2017)
Literary translation is essentially a creative process of rewriting. The translator is the author of the translation text, even if he is not the author of the original text. A translation is never a clone of the original. In translating, we do not say the same thing differently, we say something else differently, as Henri Meschonnic put it. Concepts borrowed from the field of history of translation, like historicism, passive retranslation and active retranslation are used to go against those who still erroneously think that the meaning of a literary text lies only in its words, and claim that “we translate words because there is nothing else to translate”. Against this linguistic and literary approach, the poetics approach takes into account the fact that, between the author and the reader, the translator is an active and creative agent in the process. Translating is always a “ménage Ã trois”.